Foreword: Essays in Medieval Armenian history and literature in honour of Hamlet L. Petrosyan - Kosyan, Aram (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
The remarkable professional career of Prof. Hamlet L. Petrosyan spanning over approximately five decades stands as a testament to dedication, scholarly excellence, and unwavering commitment to cultural heritage of Armenia. Born in Artsakh (Nagorno-Karabakh), a fact that would profoundly influence his life’s trajectory, Prof. Petrosyan’s journey through academic institutions and system of higher education has been both unique and exemplary. After graduating from the Department of Archaeology at Yerevan State University, he continued his academic career as a PhD student under the supervision of Prof. Babken Arakelyan, member of Academy of Sciences, writing his dissertation under this distinguished mentor’s guidance. This formative academic relationship helped shape Professor Petrosyan’s methodological approach and instilled in him a deep commitment to the study of medieval Armenian culture – a passion that would define his scholarly pursuits.